CIVIL WAR INTERVENTIONS AND THEIR BENEFITS : unequal return - Isaac M. Castellano (Lexington Books, 2015)
"The book examines how states benefit from their interventions and the distribution of intervenor benefits. Specially two questions are addressed: What are the benefits of intervention for intervening countries? And, how are benefits distributed within the intervenors society? Using evidence compiled from three case studies (El Salvador, The Philippines, and Sri Lanka), this book examines what motivated states to intervene, how they intervened, what they got from their intervention, and how the benefits of the intervention were distributed among the public. Arguing that foreign policy and security decision making is isolated from the general public, this book argues that citizens gain little from indirect interventions into civil wars." -- Back cover.